Bio-Key Based AES for Personalized Image Cryptography. (10th April 2019) - Vijayarajan, R; Gnanasivam, P; Avudaiammal, R
Abstract: In the era of multimedia technologies and rapidly growing multimedia contents, secured information transfer needs to be ensured through robust cryptography techniques. This paper presents a bio-key-generation scheme in the local environment to transfer multimedia content over vulnerable networks. To encrypt the images, one user has to ensure his/her authentication and further needs to provide a secret key for bio-key generation. Secret key aids to fetch biometric features for key formation and key expansion. Thus, the user receives an expanded key from the template database to perform encryption of a plain image. Once the cipher image is delivered to the network, the user has to repeat the same steps for decryption. This paper experiments the proposed bio-key-generation scheme with advanced encryption standard algorithm. This encryption strategy can also be used to encrypt confidential or personal images in various digital systems such as mobile phones, personal digital gadgets and so on. Various analyses ensure the robustness and the performance of the bio-key-based AES encryption scheme. Entropy, correlation coefficient, number of pixel change rate and unified average changing intensity are evaluated to ensure the effectiveness of the proposed method over other key-based encryption techniques.